Texts and intertexts in archaic and classical Greece - Kelly, Adrian 1972-; Spelman, Henry 1987- (Cambridge University Press, 2024)
Encompassing the period from the earliest archaic epics down through classical Athenian drama, this is the first concerted, step-by-step examination of the development of allusive poetics in the early Greek world. Recent decades have seen a marked rise in intertextual approaches to early Greek literature; as scholars increasingly agree on the need to read these texts in a comparative way, this only makes all the more urgent the question of how best to do so. This volume brings together divergent scholarly voices to explore the state of the field and to point the way forward. All twelve chapters address themselves to a core set of fundamental questions: how do texts generate meaning by referring to other texts and how do the poetics of allusivity change over time and differ across genres? The result is a holistic study of a key dimension of literary experience